Reviewing ecological implications of mycorrhizal fungal interactions in the Brassicaceae - Trautwig, Adam N.; Jackson, Michelle R.; Kivlin, Stephanie N.; Stinson, Kristina A. (Frontiers in Plant Science, 2023)
Mycorrhizal associations are plant-fungal mutualisms that are fairly ubiquitous and likely evolved multiple times in phylogenic history; however, some plant families have consistently been identified as non-mycorrhizal, including the Brassicaceae. In this paper, we reviewed the literature and DNA databases for potential mechanisms that preclude mycorrhizal symbioses in the Brassicaceae and for exceptions to the general observation of non-mycorrhizal status within this plant family. In instances of association between members of the Brassicaceae and arbuscular mycorrhizal fungi we posed hypotheses for why these interactions occur in the species and sites observed. Instances of inconsistent association with mycorrhizal fungi were attributed to inter-and intraspecific variations in plant biology, disagreements in vernacular, methodology contradicting historical mycorrhizal surveys, and association being a facultative, variable trait that is determined by species-site interactions. We propose further research on a) the extent of mycorrhizal association in the Brassicaceae, b) the molecular mechanisms dictating association, and c) whether Brassicaceaemycorrhizal fungal interactions result in nutrient transfer, and their particular roles in the family's distribution across heterogeneous and harsh environments. This is a provisional file, not the final typeset article Brassicaceae is generally accepted to be non-mycorrhizal, due in part to the previous historical classification by DeMars and Boerner (1996) as well as to some notable examples of mycorrhizal suppression and/or non-mycorrhizal status within the family (